THE IMPACTS OF OUTDOOR LEARNING ACTIVITIES ON CHILDRENâS SELF DEVELOPMENT - Sari, Aidha Nur Indah (ELT Perspective Jurnal Pendidikan Bahasa Inggris, 2016)
This research concentrates on investigating the impacts of outdoor learning activities in the nature based Kindergarten School of Universe Al-Ghiffari Cirebon. The research is attempted to find out whether outdoor learning activities impact childrenâs self-development or not. By doing triangulation as the method of this research, it will help to get the results more efficient, stronger, and credible. The results found that outdoor learning activities impact positively and effectively on childrenâs progress across all areas of childrenâs self developments. These areas include cognitive development, affective development, personal, social, and emotional development, and physical and behavioral development. Key words: learning,outdoor activities, outdoor education, outdoor learning, self-development